Registration of Underage Marriage Perspectives of Marriage Registrat Officer in Gorontalo City - Taufik Djuma; Zulkarnain Suleman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
This study aims to determine and analyze the views of Marriage Registrar at the Office of Religious Affairs (KUA) in Gorontalo City on the registration of underage marriages. This research is a field research. The approach used is a legal approach and a sociological approach. Data collected through observation, interviews and documentation. Furthermore, it is processed and analyzed with qualitative descriptive. The results showed that: First, the level of underage marriages in the KUA region in Gorontalo City increased every year from 2016 to 2018. Various reasons were put forward by the parties, both prospective brides and families to be able to carry out underage marriages; Second, in principle the Marriage Registrar in Gorontalo City understands and implements the marriage registration rules based on the Minister of Religion Regulation No. 19 of 2018 about Marriage Registration.